Green Synthesis and Characterization of Silver Nanoparticles from Randia dumetorum Roots for Drug Delivery Applications - Madhuri Nalawade; Subrata Kundu; Amit Kasabe (International Journal of Medical Toxicology and Legal Medicine, 2024)
Nanoparticles derived from Randia Dumetorum Roots were successfully synthesized and thoroughly characterized to investigate their potential as innovative drug delivery systems. These nanoparticles demonstrated favorable characteristics, including an optimal particle size ranging between 1-100 nm, high entrapment efficiency (70–90%), and sustained drug release profiles, achieving 89–95% release within 60 minutes in phosphate-buffered saline (pH 7.4). Stability studies highlighted the robustness of the optimized formulation (NF4), which maintained consistent particle size, zeta potential, and entrapment efficiency over 12 weeks of storage at 4°C. Surface morphology analysis using Scanning Electron Microscopy (SEM) confirmed the spherical structure of the nanoparticles with minimal aggregation, aligning with particle size measurements obtained through light scattering techniques. Formulations designed for topical applications exhibited excellent performance, with suitable pH (6.2) for skin compatibility, enhanced spreadability (29±0.34 cm²), and desirable viscosity (1248±0.632 cps), ensuring ease of application and patient compliance. The predictive accuracy of critical formulation parameters, such as pH and spreadability, was validated through statistical analysis using ANOVA, further strengthening the reliability of the study outcomes. The results underscore the promise of Randia Dumetorum-based nanoparticles as an effective platform for drug delivery, capable of improving therapeutic efficacy and patient outcomes. Future research directions include in vivo clinical validation to assess safety and bioavailability, exploration of molecular mechanisms underlying the therapeutic benefits, development of scalable production methods, and optimization for broader applications, such as oral or injectable dosage forms. These advancements will help unlock the full potential of Randia Dumetorum nanoparticles in modern medicine.